Automated immunoassays for 25-hydroxyvitamin D (25-OHD): Do plasticisers interfere?. Issue 148 (April 2015) - Carter, G.D.; Jones, J.; Ketheeswaran, M.; Shannon, J.; Singh, B.; Kearney, E.; Berry, J.L.
Highlights: DEQAS is an accuracy based quality assessment scheme for vitamin D metabolites. Blood collection bags may leach plasticisers that could interfere in 25-OHD assays. 3 automated assays showed no difference in blood collected in bags or glass tubes. Materials leached from plastic bags caused no interference in these immunoassays. Abstract: The international quality assessment scheme for vitamin D metabolites (DEQAS) was established in 1989. The scheme involves the quarterly distribution of 5 serum samples prepared from blood collected in plain plastic bags. Following transfer of the donors to a clinic using different bags, sera were found to contain a contaminant that interfered in both the local LC–MS/MS assay and the NIST reference measurement procedure for 25-OHD. It seemed likely that the contaminant was a substance, possibly a plasticiser, leached from the plastic bag. It was subsequently suggested that the unidentified contaminant might also cause interference in certain automated non-extraction assays for 25-OHD. This was investigated in 3 automated immunoassays by comparing serum 25-OHD results from blood collected simultaneously into plain glass tubes and plastic bags. There was no significant difference in results, indicating that the leached substance had no effect on any of the 3 immunoassays examined.